Comparative Analysis on the Translation of the Academic Handbook of University of Mataram Using ChatGPT and Professional Translation - Rilasti, Fifi; Junaidi, Ahmad; Putera, Lalu Jaswadi (Journal of English Education Forum (JEEF), 2024)
Translation can be interpreted as the concept of transferring meaning from one language to another according to the meaning the author wants to convey. This study aims to find out the aspect of the differences between translation using ChatGPT and Professional in the Academic Handbook of University of Mataram and to determine the more accurate translation between ChatGPT and Professional translation. This study used a qualitative method. The researcher applied a comparative analysis technique of the results of the ChatGPT and Professional translations of the Academic Handbook of University of Mataram. The results of this research show that of the three translation techniques applied, borrowing techniques were used 147 times, adaptation techniques were used 90 times and literal translation techniques were used 86 times. After conducting a comparative analysis, the researcher then tested the level of accuracy of the analysis data results using House's theory (1997). Then, the results of the accuracy level data test show that the translation by Professionals is more accurate than the ChatGPT translation results.